Pengembangan bahan ajar e-book akuntansi keuangan kelas XII SMK pada materi aset tetap berwujud berbasis pendekatan saintifik - Fahira Qotrunnada; Joni Susilowibowo (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2021)
In 21st century education, the use of information technology is needed to facilitate learning activities, especially in the development of learning materials. For example, the use of electronic teaching materials in the form of e-books. The research was carried out with the aim of developing and analyzing the feasibility of the financial accounting e-book teaching material for class XII SMK in the material of tangible fixed assets based on a scientific approach as well as knowing the responses of students after being given e-book teaching materials. The 4D model by Thiagarajan, Semmel and Semmel is used in this research and development (R&D) research. The steps taken are define, design, develop, while disseminate was not carried out. The research data were analyzed using quantitative descriptive analysis techniques. Obtaining the feasibility of the results of this study revealed that the validity of the material, language, and graphics were categorized as very feasible. A total of 20 students from class XII AKL SMK Rajasa Surabaya gave their responses to the e-book teaching material as a limited trial implementation that obtained a very well-understood interpretation. Thus, the e-book teaching materials for Financial Accounting class XII SMK on tangible fixed assets based on a scientific approach can be used in the learning process